EFFECT OF LOCAL AMF INOCULATION AND PHOSPHATE FERTILIZER RATES ON PRODUCTIVITY AND LAND USE EFFICIENCY OF SUGARCANE–SOYBEAN INTERCROPPING SATURATED SOIL CULTIVATION ON TIDAL LAND - Sefrila, Marlin; Ghulamahdi, Munif; Melati, Maya; Mansur, Irdika (LPPM Universitas Jambi, 2026)
Tidal lands have considerable potential for sugarcane expansion but are constrained by low phosphorus availability, soil acidity, and low productivity under conventional systems. Despite advances in water-saturated cultivation and the use of arbuscular mycorrhizal fungi (AMF), their combined effects with phosphate fertilization in sugarcane–soybean intercropping systems remain insufficiently understood. This study aimed to evaluate the effects of AMF inoculation and phosphate fertilizer rates, as well as their interaction, on crop productivity and land use efficiency. A field experiment was conducted on tidal land in Banyuasin, South Sumatra, using a randomized complete block design with two factors and three replications. The treatments consisted of AMF inoculation (without and with local AMF derived from maize) and phosphate fertilizer rates (0, 36, 72, and 108 kg ha⁻¹ P₂O₅) under a 4-month water-saturated cultivation system. Productivity and land equivalent ratio (LER) were used as key indicators. The results showed that the interaction between AMF inoculation and phosphate fertilizer rates was not significant for sugarcane productivity. However, AMF inoculation significantly increased the productivity of both sugarcane and soybean in intercropping and monoculture systems. In contrast, phosphate fertilizer rates did not significantly affect land use efficiency. The intercropping system consistently produced LER values greater than 1 (1.55–1.73), indicating higher land-use efficiency than monoculture systems. These findings demonstrate that AMF inoculation plays a more important role than phosphate fertilization in improving crop productivity under water-saturated tidal conditions.